Diary of a Mental Health Peer Worker: Findings From a Diary Study Into the Role of Peer Work in a Clinical Mental Health Setting - Wyder, Marianne; Roennfeldt, Helena; Parker, Stephen; Vilic, Gabrielle; McCann, Karen; Ehrlich, Carolyn; Dark, Frances Louise (Frontiers in Psychiatry, 2020)
Introduction: The importance of peer support workers in mental health care delivery has been extensively advocated for in mental health policy frameworks. The evidence base for peer work is still developing. Information around how peer workers conceptualise their role is critical to inform the implementation of peer workers in clinical settings. This study explores the experience of paid peer support workers integrated within a clinically-operated community-based residential rehabilitation service for people diagnosed with a mental health disorder experiencing challenges living independently in the community. Methods: A general inductive approach was taken in the analysis of diaries completed by a newly employed peer workforce. These diaries focussed on what they viewed as significant interactions in fulfilling their role. Composite vignettes were generated to illustrate key themes. Findings: 36 diary entries were provided; these reported unplanned and spontaneously occurring interactions. Peer workers emphasised the importance of connecting with people while they were engaging in everyday activities as an opportunity for personal growth of the residents. The diaries also focussed on the peer workers’ ability to connect and establish trust by sharing similar experiences with residents or family members. Peer workers also believed that they brought a different perspective than clinical staff and were able to refocus attention from clinical diagnoses and symptoms to other aspects of the resident’s lives. Discussion: Peer support workers described their work as flexible, responsive and adaptable to the resident’s needs. They believed that their roles brought a different lens to interactions on the unit and fostered a more inclusive and personal way of working for the team. Conclusion: To ensure that peer workers can engage authentically with residents and family members, it is critical that the role and principles of peer work are valued and understood by all.